Diagnostic considerations for gastrointestinal stromal tumors with altered immunophenotype following Imatinib treatment: A case report and literature review - Jihuan Chen; Liz M. Yang; Jonathan Somma; Yujun Gan; Zengying Wu; Zhiyan Fu (Human Pathology Reports)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors in the gastrointestinal tract and have a high rate of recurrence and metastasis. Using an immunohistochemical (IHC) panel including KIT/CD117 and DOG1 allows for accurate diagnosis in more than 98% of cases. However, after tyrosine kinase inhibitor treatment, some cases can exhibit histologic dedifferentiation and loss of KIT/CD117 and DOG1 expression that may cause difficulty in confirming recurrent or persistent disease. We present such a case of an Imatinib treated, CD117 and DOG1 dual negative, metastatic GIST to the liver in a 55-year-old female which required molecular analysis to confirm the diagnosis. Awareness and recognition of this phenomenon is crucial for the accurate diagnosis and management of patients with GISTs.